Exogenity of Asian Financial Markets and Possible Contagion: Some Empirical Evidence - Sahu, Dhananjay; Singh, Basant Kumar (Indian Journal of Finance, 2011)
The present paper is explicitly intended to explore the dynamic interactions among these emerging markets in Asia to study their level of integration. The objective of the paper is to understand the dynamic inter-linkages between four emerging equity markets in Asia viz. India, South Korea, Taiwan and Philippines and to understand whether the stock markets are interlinked. The data employed in this paper comprises of daily closing prices of CNX Nifty (India), SE (Philippines), TAIEX (Taiwan) and KOPSI200 (South Korea) for the sample period April 01, 1998 to March 31, 2008. To test the hypothesis, we have employed Johansen's cointegration test and Granger causality test. The results of the analysis indicate that there is no cointegration between the capital markets of India, Philippines, Taiwan and South Korea and there exists long run equilibrium between these markets, though the results exhibit certain mild and short term unidirectional as well as bidirectional causal relationship between the capital markets chosen for the analysis. The implication of the result is that these markets do not yet warrant any immediate concern for any possible contagion and the market participants can reap the benefit of portfolio diversification by investing in these markets.